Phenomenological Review of the Issue of Political Apathy of Indonesia's Young Generation - Iskandarsyah Siregar (Britain International for Academic Research (BIAR-Publisher), 2024)
This article explores the growing political apathy among Indonesia's young generation, which poses significant challenges to the nation's democratic future. Utilizing a phenomenological approach, the study delves into the lived experiences of Indonesian youth to uncover the factors contributing to their disengagement from political processes. Key factors identified include disillusionment with the political system, the influence of digital media, socio-economic pressures, cultural and familial expectations, and educational shortcomings. The article also discusses the implications of this apathy for Indonesia's democracy and proposes recommendations to re-engage the youth in the political process. These include reforming civic education, leveraging digital media for positive engagement, addressing socio-economic barriers, promoting a culture of political participation, strengthening political institutions, and encouraging youth leadership.